The Living QS. Saba`: 13 among Javanese Moslem Sculptors - Ahmad Mustofa (UIN Sunan Kalijaga Yogyakarta, 2025)
Every depiction of living creature is forbidden in Islam, whether in the form of paintings or statues. The prohibition that originates from the hadith has become an established doctrine in Islam, even then created a unique branch of art in Islam namely aniconism. However, there is a group of Muslim sculptors in the Prumpung Magelang area who still preserve their culture as sculptors without having to confront Islamic teachings either in the philosophical or practical domains. This study aims to examine and analyze the negotiations of Muslim sculptors in Prumpung Magelang regarding the doctrine of the prohibition of sculpting in Islam. By utilizing reception theory, this field research is located in the Prumpung Magelang area, with Muslim sculptors as the research subjects, and therefore primary data is obtained based on in-depth interviews with informants consisting of key figures in Muslim sculptors and those associated with them. This study found that Muslim sculptors were aware of the existence of the doctrine that prohibits carving statues in the form of living creatures in Islamic teachings, which only applies to statues that are converted into idols (used as objects of worship). Meanwhile, the statue making industry in the Prumpung Magelang area is not at all related to religious worship and certain beliefs, therefore it is permitted. This perspective is identical (linear) with the status of the existence of statues mentioned in the Qur'an, that their existence is permitted as long as they are not used as objects of worship as in QS. Saba`:13.